The effect of viscosifier, fluid loss control and emulsifier agents toward ester based mud system - Shaziera Omar, 1990; Abdul. Razak Ismail; Fakulti Kejuruteraan Petroleum dan Tenaga Diperbaharui (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum))-Universiti Teknologi Malaysia, 2012